Nourishing Ourselves: A zine for social justice activists - Jivraj, Suhraiya; Alsaraji, Alaa; Manzoor-Khan, Suhaiymah (feminists@law, 2023)
An invitation to reconnect with the joy and playfulness at the heart of your creativity beyond the pressures of productivity, profit, or ‘impact’. Nourishing Ourselves explores the importance of using creativity as a way to reconnect to ourselves and our wellbeing at a time when many are expected to use our visual, oral, written, or other stories to “shed light on”, “represent”, or produce counter-narratives to salvage our humanity. The zine asks what would happen if we had the time to create for the sake of tending to ourselves and each other, reconnecting to the playfulness which makes creative expression possible, without forcing it into a “product”. Our publication comes out of a one-day workshop curated by artist Alaa Alsaraji and writer Suhaiymah Manzoor-Khan who were commissioned to develop a session for social justice activists using arts-based methods in their work. The commission from Dr Suhraiya Jivraj aimed to explore how activists’ use of creative expression could transform social justice, as well as build the capacity of participants. However, through curation, the workshop that emerged was itself a reflection of the possibilities of co-production. Instead of focusing on using creative methods for social justice in an output-oriented way, Alaa and Suhaiymah considered our own relationship to activism in our art. We recognised that our capacity to work for social justice was often depleted by the pressure to use creativity for those same ends. We therefore explored ways of working with creativity that would feel replenishing for us, instead. This enabled a rare experience of facilitating without expectation of ‘end-product’ or extraction from participants. Instead of considering creativity as simply a tool, we curated a space to experiment, play and falter. For how are we to imagine, let alone build a just world, without reconnecting to the feelings that enable creativity in the first place? We invite you to explore the zine, enjoy the artwork by participants, try the guided activities and share your reflections and creative expressions with us via this padlet or email to: s.jivraj@kent.ac.uk.